Interaction between Mesenchymal Stem Cells and Intervertebral Disc Microenvironment: From Cell Therapy to Tissue Engineering - Papalia, Rocco; Russo, Fabrizio; Ambrosio, Luca; Vadalà, Gianluca; Denaro, Vincenzo (Stem cells international, 2019)
Low back pain (LBP) in one of the most disabling symptoms affecting nearly 80% of the population worldwide. Its primary cause seems to be intervertebral disc degeneration (IDD): a chronic and progressive process characterized by loss of viable cells and extracellular matrix (ECM) breakdown within the intervertebral disc (IVD) especially in its inner region, the nucleus pulposus (NP). Over the last decades, innovative biological treatments have been investigated in order to restore the original healthy IVD environment and achieve disc regeneration. Mesenchymal stem cells (MSCs) have been widely exploited in regenerative medicine for their capacity to be easily harvested and be able to differentiate along the osteogenic, chondrogenic, and adipogenic lineages and to secrete a wide range of trophic factors that promote tissue homeostasis along with immunomodulation and anti-inflammation. Several in vitro and preclinical studies have demonstrated that MSCs are able to acquire a NP cell-like phenotype and to synthesize structural components of the ECM as well as trophic and anti-inflammatory mediators that may support resident cell activity. However, due to its unique anatomical location and function, the IVD presents distinctive features: avascularity, hypoxia, low glucose concentration, low pH, hyperosmolarity, and mechanical loading. Such conditions establish a hostile microenvironment for both resident and exogenously administered cells, which limited the efficacy of intradiscal cell therapy in diverse investigations. This review is aimed at describing the characteristics of the healthy and degenerated IVD microenvironment and how such features influence both resident cells and MSC viability and biological activity. Furthermore, we focused on how recent research has tried to overcome the obstacles coming from the IVD microenvironment by developing innovative cell therapies and functionalized bioscaffolds.